Better care: reducing length of stay and bed occupancy on an older adult psychiatric ward. Issue 4 (1st November 2018) - Adlington, Katherine; Brown, Juliette; Ralph, Laura; Clarke, Alan; Bhoyroo, Tim; Henderson, Michael; Boora, Farai; Aurelio, Marco; Fawzi, Waleed
Abstract : Background: Length of stay and bed occupancy are important indicators of quality of care. Admissions are longer on older adult psychiatric wards as a result of physical comorbidity and complex care needs. The recommended bed occupancy is 85%; levels of 95% or higher are associated with violent incidents on inpatient wards. Methods: We aimed to reduce length of stay and bed occupancy on Leadenhall ward, a functional older adult psychiatric ward serving a population of just under 40 000 older adults in two of the most deprived areas of the UK. At baseline in October 2015, the average length of stay was 47 days, and bed occupancy was at 77%. We approached the problem using quality improvement methods, established a project team and proceeded to test a number of changes over time in line with the driver diagram we produced. Results: In 12 months, length of stay was reduced from an average 47 to an average 30 days and bed occupancy from 77% to 54%. At the end of 2016, the closure of some beds effected this calculation and we added an additional outcome measure of occupied bed days (OBD) better to assess the impact of the work. OBD data show a decrease over the course of the project from 251 to 194 bed days (a reduction of 23%). Conclusion: The most effective interventions to address length of stay and bed occupancy on an older adult functional mental health ward were the daily management round and the high-level management focus on longer-stay patients. The work depended on an effective community team and on the support of the quality improvement programme in the trust, which have led to sustained improvements.